(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract. This manuscript introduces a generalization of the linear failure rate (LFR) distribution, called the new exponential linear failure rate (NExLFR) distribution, with an application to the strengths of glass fibers. The new model is highly flexible and can be effectively applied in various fields. We present several mathematical properties of the new model, including the density function, cumulative distribution function, survival function, and hazard rate function of the NExLFR distribution. Method of maximum likelihood estimation is discussed to estimate the unknown parameters of the model. Finally, to showcase the flexibility of this distribution and for illustrative purposes, we apply it to a real dataset and NExLFR shows perfect fit for the strengths of glass fibers data.